Variability of Shelf Growth Patterns along the Iberian Mediterranean Margin: Sediment Supply and Tectonic Influences - Ruth Durán; Francisco José Lobo; Marta Ribó; Marga García; Luis Somoza (Geosciences, 2018)
Clinoform depositional features along the Iberian Mediterranean margin are investigated in this study, with the aim of establishing the causes of their varied shapes and other characteristics. We have analyzed the broad-scale margin physiography and seismic stratigraphic patterns based on high-resolution bathymetric data and previously interpreted seismic data. In addition, we have evaluated regional supply conditions and the uplift-subsidence regime of the different shelf sectors. The upper Quaternary record is strongly dominated by shelf-margin regressive wedges affected by the prevailing 100 ka cyclicity. However, the margins exhibit considerable lateral variability, as the result of the balance between the amount of sediment supply and the uplift-subsidence relationship. Three major shelf sectors with distinct morpho-sedimentary features have been defined. The relatively narrow northern shelves (Roses, La Planassa and Barcelona) are supplied by discrete river outlets that collectively constitute a linear source and are mainly affected by tectonic tilting. The wide middle shelves (Ebro Shelf, the Gulf of Valencia, and the Northern Arc) receive the sediment supply from the large Ebro River and other medium rivers. Although the tectonic regime changes laterally (strong subsidence in the north and uplift in the south), shelf growth is maintained by lateral advection of sediments. The southern shelves (the Southern Arc and the northern Alboran Shelf) are very abrupt and narrow because of the uplifting Betic Cordillera, and the torrential fluvial regimes that determine a very efficient sediment by-pass toward the deep basin. Submarine canyons deeply incised in the continental margin constitute a key physiographic feature that may enhance the transport of sediment to the deep sea or individualize shelf sectors with specific sedimentation patterns, as occurs in the Catalan margin.